1992
DOI: 10.1152/ajprenal.1992.263.5.f915
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of tumor necrosis factor-induced increase in renal (LLC-PK1) transepithelial permeability

Abstract: Tumor necrosis factor-alpha (TNF) causes a spontaneously reversible increase in tight junction permeability. TNF was the only cytokine tested that produced this effect. The effect on transepithelial permeability proceeds in four distinct phases: 1) a 60- to 90-min delay from time of application of TNF, 2) a rapid decrease in transepithelial resistance, 3) a recovery of transepithelial resistance to control level within 1 h, and 4) a further increase of transepithelial resistance above control levels. The recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 0 publications
5
40
1
Order By: Relevance
“…Tumor necrosis factor-α (TNF-α) appears to play an important role in regulating intestinal epithelial barrier function since TNFα-neutralizing antibodies restored barrier function in Crohn's disease patients (Suenaert et al, 2002). Exposure of cultured epithelial monolayers to TNF-α in vitro caused epithelial barrier loss (Mullin et al, 1992;Marano et al, 1998). In another study, exposure of cultured epithelial monolayers to TNF-α increased MLC phosphorylation which was associated with impaired barrier function (Zolotarevsky et al, 2002).…”
Section: The Leaky Epithelial Barrier In Intestinal Diseasesmentioning
confidence: 99%
“…Tumor necrosis factor-α (TNF-α) appears to play an important role in regulating intestinal epithelial barrier function since TNFα-neutralizing antibodies restored barrier function in Crohn's disease patients (Suenaert et al, 2002). Exposure of cultured epithelial monolayers to TNF-α in vitro caused epithelial barrier loss (Mullin et al, 1992;Marano et al, 1998). In another study, exposure of cultured epithelial monolayers to TNF-α increased MLC phosphorylation which was associated with impaired barrier function (Zolotarevsky et al, 2002).…”
Section: The Leaky Epithelial Barrier In Intestinal Diseasesmentioning
confidence: 99%
“…50,51 There have been many hypotheses as to the mechanism of TNF-induced barrier dysfunction, including single cell epithelial apoptosis, 52 nonapoptotic mechanisms, 53 and reduced transcription of tight junction proteins. 54 Although a role for each of these processes cannot be excluded, a series of recent reports suggests that TNF regulates tight junction permeability via cytoskeletal contraction.…”
Section: Tnf Regulates Barrier Function In Vitromentioning
confidence: 99%
“…Since macrophages, even metabolically stressed macrophages (Table 1), release a variety of mediators following activation, we opted to focus subsequent studies on TNF-␣, a factor which has been implicated in IBD and has been shown to affect endothelial (11,12), gut (38), and kidney (25,26) epithelial permeability.…”
Section: Dnp Causes Metabolic Stress In Differentiated Macrophagesmentioning
confidence: 99%
“…This loss of epithelial integrity was inhibited by neutralizing antibodies to TNF-␣. Although TNF-␣ can directly increase paracellular permeability across selected renal and enteric epithelial cell lines (25,38), by itself TNF-␣ has minimal direct effects on the barrier properties of T84 cell monolayers (4,23), indicating that TNF-␣ was either activating LPMC and/or working in concert with other mediators released from the LPMC to increase the permeability to T84 cell monolayers (50).…”
mentioning
confidence: 99%